New distributional, biological and taxonomic information on the genus Eulophinusia Girault (Hymenoptera: Eulophidae) - Hansson, Christer; Hallwachs, Winnie; Janzen, Daniel H. (Zootaxa, 2021)
The genus Eulophinusia Girault (Hymenoptera: Eulophidae), previously known from Australia and India, is newly recorded from the Americas (Canada, Costa Rica, Dominican Republic). The morphological diagnosis of the genus is enhanced through the discovery of an unnoticed and unique feature - an intricate jigsaw-like microsculptural pattern on the mesoscutellum. The new species described here, Eulophinusia andreamezae Hansson, is a hyperparasitoid. The majority of the Costa Rican specimens of this species were reared from pupae of Hypomicrogaster largus Valerio (Braconidae: Microgastrinae) that had parasitized a caterpillar of Anadasmus Janzen11 (Lepidoptera: Depressariidae) feeding on Ocotea insularis (Lauraceae).